HUBUNGAN MINAT BELAJAR SISWA KELAS X LINTAS MINAT PADA MATA PELAJARAN BIOLOGI TERHADAP HASIL BELAJAR SISWA DI MADRASAH ALIYAH NEGERI (MAN) TARAKAN - Leila Leila; Aidil Adhani; Vlorensius Vlorensius (Program Studi Pendidikan Biologi Universitas Borneo Tarakan, 2021)
This research was intended to measure the relationship between students’ interest in Biology subject to students’ learning outcomes at class X cross-interest students of Madrasah Aliyah Negeri (MAN) Tarakan. The design of the research was a survey with descriptive correlational quantitative data. This research population was 184 students of class X, cross-interest students of Madrasah Aliyah Negeri (MAN) Tarakan, and the research sample was 70 students. The sample was determined using the nonprobability sampling technique from purposive sampling. Overall data were obtained based on scores from students’ interest questionnaires and multiple choice questions, then analyzed by Pearson Product Moment Correlation Test and Linear Regression Test. There was no relationship between students’ interest in Biology learning outcomes with a significance value of 0.407. Keywords: Interest, Cross-Interests, Biology Learning Outcomes